2011
DOI: 10.1348/000712610x498958
|View full text |Cite
|
Sign up to set email alerts
|

Predicting beauty: Fractal dimension and visual complexity in art

Abstract: Visual complexity has been known to be a significant predictor of preference for artistic works for some time. The first study reported here examines the extent to which perceived visual complexity in art can be successfully predicted using automated measures of complexity. Contrary to previous findings the most successful predictor of visual complexity was Gif compression. The second study examined the extent to which fractal dimension could account for judgments of perceived beauty. The fractal dimension mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
217
7
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(251 citation statements)
references
References 54 publications
22
217
7
5
Order By: Relevance
“…Moreover, Redies et al used the Histogram of Orientation Gradients (HOG) approach to calculate two other aesthetic measures, complexity and anisotropy. In support of previously published ideas, their results showed that intermediate levels of complexity characterize visual artworks on average [Berlyne 1974;Forsythe et al 2011]. The anisotropy of orientation gradients in visual artworks is about as low as in images of diverse natural patterns and scenes (see also [Koch et al 2010]).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, Redies et al used the Histogram of Orientation Gradients (HOG) approach to calculate two other aesthetic measures, complexity and anisotropy. In support of previously published ideas, their results showed that intermediate levels of complexity characterize visual artworks on average [Berlyne 1974;Forsythe et al 2011]. The anisotropy of orientation gradients in visual artworks is about as low as in images of diverse natural patterns and scenes (see also [Koch et al 2010]).…”
Section: Introductionsupporting
confidence: 79%
“…This type of research is in line with the notion that aesthetic artworks share specific and universal properties, which reflect functions of the human visual system in particular and of the human brain in general [Zeki 1999;Reber et al 2004;Redies 2007]. Over the years, different research groups proposed several properties that characterize aesthetic paintings [Birkhoff 1933;Arnheim 1954;Berlyne 1974;Graham and Field 2007;Redies et al 2007;Rigau et al 2008;Forsythe et al 2011]. For example, Redies et al [Redies et al 2007] and Graham and Field [Graham and Field 2007] have shown that, on average, log-log plots of the radially averaged 1d power spectrum of greyscale images tend to drop according to a power law, similar to results that have been described for natural scenes [Field et al 1987;Burton and Moorhead 1987].…”
Section: Introductionsupporting
confidence: 62%
“…Hagerhall, Purcell, and Taylor [46] found that fractal characteristics of landscape silhouette outlines reliably predict landscape preferences. Fractal characteristics provide a consistent measure of complexity, and were shown to account for judgments of perceived beauty in visual art [47]. Here, we make the prediction that the "symmetry of things in a thing" in 2D fractal objects plays a decisive role in our perception of their aesthetic content and thereby influences visual preference judgments.…”
Section: Nature-inspired Design and The Symmetry Of "Things In A Thing"mentioning
confidence: 86%
“…This is especially important in aesthetics research, where there have been claims of universality in preference for patterns of moderately low complexity [23,26,[34][35][36][37]. To test this hypothesis, it is necessary to be able to translate the units of measurement of researchers who alternately use D [22,25,26,28,29,31,[33][34][35][36][37][38][39][40], β [14,24,30,32,[41][42][43][44][45][46], or, infrequently, both [23,27]. The crux of the problem, perhaps, is that D is a general parameter that quantifies complexity in a variety of patterns, whereas β is limited (at least in practice) in its ability to quantify some patterns' complexity.…”
Section: D(mountain Edgementioning
confidence: 99%